Mechanical Performance and Sustainability Potential of Concrete Incorporating Waste Polytetrafluoroethylene Fibers - Lilis Zulaicha; Oggi Heicqal Ardian; Anggi Hermawan (CV FOUNDAE, 2026)
This study investigates the feasibility of utilizing waste polytetrafluoroethylene (PTFE) fibers as a recycled additive in concrete to support plastic waste valorization and sustainable construction material development. Waste PTFE fibers obtained from industrial seal production were mechanically processed into irregular fiber-like particles with sizes of approximately 4–6 mm and incorporated into concrete mixtures at 0.2%, 0.4%, 0.6%, and 0.8% by weight of concrete. The effects of PTFE fiber addition on workability, splitting tensile strength, and flexural strength were evaluated using cylindrical and beam specimens tested according to SNI and ASTM standards. The results show that increasing PTFE fiber content reduced concrete workability, as indicated by a decrease in slump from 125 mm for the control mixture to 75 mm for the mixture containing 0.8% PTFE fibers. The incorporation of untreated PTFE fibers also decreased mechanical strength. Compared with the control concrete, splitting tensile strength decreased by 6.924%–18.474%, while flexural strength decreased by 15.409%–32.060%. This reduction is attributed to the smooth, hydrophobic, chemically inert, and low-friction surface characteristics of PTFE, which weaken adhesion between the fibers and the cementitious matrix and reduce load-transfer efficiency. Although untreated waste PTFE fibers did not improve the tensile-related mechanical performance of concrete, their use may contribute to plastic waste utilization in construction materials. Further surface treatment, fiber modification, and mix design optimization are required before waste PTFE fibers can be effectively applied as reinforcing materials in sustainable concrete.